Diseminasi Rak Pembibitan Biji Bawang Merah Dengan Teknologi Pencahayaan dan Penyiraman Terkendali - Pratiwi, Artdhita Fajar; Utami, Sari Widya; Aji, Galih Mustiko; Hidayanto, Fajar (Politeknik Negeri Cilacap, 2025)
The continued reliance on shallot seeds is a significant challenge, primarily due to the high production costs associated with seed cultivation. To address the high production costs associated with shallot seeds, horticultural farmers within the Rejeki Lancar Farmer Group have endeavored to cultivate shallots from seeds. Nevertheless, the efficacy of the seeding technique remains relatively low. This is attributable to the specific land and climate conditions that prevail in this region. Considering the challenges encountered by this group, the proposed community service activities prioritize the acceleration of seedling growth, the enhancement of seedling quality, and the optimization of production costs for shallot seeds. This is achieved through the construction of a seedling rack equipped with artificial light. This community service activity utilizes a problem-solving approach based on the existing issues within the partner group, combined with a technology-based solution approach. The implementation of the community service program begins with observations at the partner site, followed by discussions with the partner regarding needs analysis and the suitability of the technological resources mastered by the community service team. This is followed by the preparation of technological media/tools, dissemination and training on the operation of the tools, and an evaluation of the activities. This activity demonstrates the high level of interest among residents in accelerating the production of red onion seeds from seeds. During the trial process, within two days in the germination rack, the growth of the seeds was observed to be significantly faster compared to traditional seedling production, which typically requires more time.